2019
DOI: 10.14814/phy2.14155
|View full text |Cite
|
Sign up to set email alerts
|

Influence of shortened recovery between resistance exercise sessions on muscle‐hypertrophic effect in rat skeletal muscle

Abstract: Resistance exercise training induces muscle hypertrophy, and recovery between sessions is one of the major determinants of this effect. However, the effect of the recovery period between sessions on muscle hypertrophy following resistance exercise training remains unclear. To elucidate the effect of recovery period on hypertrophy, in the present study, we investigated changes in protein degradation systems and hypertrophic responses in rat skeletal muscle to resistance training with variable recovery periods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 46 publications
2
26
0
1
Order By: Relevance
“…We did not observe any significant difference in the protein expression of PGC‐1α between the groups, although the expression levels of OXPHOS proteins were significantly decreased by functional overload regardless of rapamycin administration. Chronic muscle contraction has been demonstrated to enhance expression levels of PGC‐1α and OXPHOS proteins (Kitaoka et al, 2015; Ogasawara et al, 2016; Takegaki, Ogasawara, et al, 2019). While these previous studies employed a model of muscle hypertrophy induced by 4 weeks of muscle contraction, our study employed a model of rapid muscle hypertrophy in 14 days, and we believe that adequate adaptation of mitochondrial biogenesis and mitochondrial content would not occur in this short‐term muscle hypertrophy model.…”
Section: Discussionmentioning
confidence: 99%
“…We did not observe any significant difference in the protein expression of PGC‐1α between the groups, although the expression levels of OXPHOS proteins were significantly decreased by functional overload regardless of rapamycin administration. Chronic muscle contraction has been demonstrated to enhance expression levels of PGC‐1α and OXPHOS proteins (Kitaoka et al, 2015; Ogasawara et al, 2016; Takegaki, Ogasawara, et al, 2019). While these previous studies employed a model of muscle hypertrophy induced by 4 weeks of muscle contraction, our study employed a model of rapid muscle hypertrophy in 14 days, and we believe that adequate adaptation of mitochondrial biogenesis and mitochondrial content would not occur in this short‐term muscle hypertrophy model.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, repetitive resistance exercise with excessively short recovery is known to highly activate mTORC1 [2][3][4]. On the other hand, as mentioned above, this type of exercise training does not induce the acute activation of muscle protein synthesis and chronic muscle hypertrophy even though mTORC1 is highly activated [2][3][4]. These facts indicate the possibility that an excessively shortened recovery influences the downstream targets of the mTORC1 pathway.…”
Section: Introductionmentioning
confidence: 98%
“…A recent study reported that mTORC1 plays a minor role in the acute activation of muscle protein synthesis but is essential for muscle hypertrophy induced by chronic mechanical overload [8]. Additionally, repetitive resistance exercise with excessively short recovery is known to highly activate mTORC1 [2][3][4]. On the other hand, as mentioned above, this type of exercise training does not induce the acute activation of muscle protein synthesis and chronic muscle hypertrophy even though mTORC1 is highly activated [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations